Improving Marketing Performance Through the Role of Business Networks as Mediating Variables in MSMEs Bakery Products - Putri Cyintia Anggraeni; Meutia Meutia; Hayati Nupus (Asean International Journal of Business, 2026)
Purpose - This study aims to examine the effect of proactive orientation and risk-taking orientation on marketing performance and the role of business network as a mediating variable in Micro MSMEs of bakery products in Serang City. Methodology– This study used quantitative methods, instrument testing using SPSS-26, inferential testing, and hypothesis testing using SEM-PLS. The population in this study was 1,075, and the sample used in this study was selected using purposive sampling, resulting in 98 samples that met the criteria. Findings – It was found that proactive orientation and risk-taking orientation have positive significant to marketing performance and business network, business network has positive insignificant effect on marketing performance and business network does not mediate the relationship between proactive orientation to marketing performance, and business network does not mediate the relationship between risk-taking orientation to marketing performance. Novelty – The novelty in this research is the involvement of business network as mediators in MSMEs in the food sector, especially dry bakeries in Serang City.